Concomitant surgical ablation for atrial fibrillation (AF) in patients with significant atrial dilation >55 mm. Worth the effort?. Issue 1 (December 2015) - Pecha, Simon; Hakmi, Samer; Subbotina, Irina; Willems, Stephan; Reichenspurner, Hermann; Wagner, Florian
Abstract Background Concomitant Surgical AF ablation is an established procedure, recommended in guidelines. However many surgeons are reluctant to perform AF ablation in patients with significantly enlarged left atrium. We therefore analyzed outcomes of patients with left-atrial diameter >55 mm undergoing concomitant AF ablation. Methods Between 05/2003 and 12/2012 124 patients with significantly enlarged left-atrium >55 mm underwent concomitant surgical AF ablation. Rhythm monitoring was accomplished by implantable loop recorder (ILR) interrogation (n = 54), or 24-h Holter-ECG (n = 70). Successful ablation was defined as AF Burden <0.5 % in ILR interrogation or absence of AF episode >30 s in 24-h Holter-ECG. Primary endpoint of the study was freedom from AF at 12 months follow-up. Results Mean patient's age was 65.7+/−9.6 years, 69.4 % were male. No major ablation or ILR related complications occurred. Mean LA diameter was 60.7+/−4.4 mm. Survival rate at one-year follow up was 94.4 %. 11 (8.8 %) patients received additional catheter-based ablation, while 23 (18.5 %) had an electrical cardioversion during follow-up period. Overall freedom from AF rate after one-year follow-up was 64.4 % and 59.4 % off antiarrhythmic drugs respectively. Logistic regression analysis identified preoperative paroxysmal AF, duration of AF and LA diameter > 70 mm as predictors for rhythm outcome at 12 months follow-up. Conclusion In this patient cohort with significantly enlarged LA diameter, concomitant surgical AF ablation provided freedom from AF of 64.4 % after one-year follow-up. However in this patient population, an accurate postoperative care with interventions like medical or- electrical cardioversion and additional catheter based ablation is necessary to achieve satisfactory results.